The Impact of Arab Spring on Hiring and Separation Rates in the Tunisian Labour Market - Ilham Haouas; Almas Heshmati (Institute for the Study of Labor (IZA), 2015)
This paper analyses the hiring and separation rates in Tunisia before and after the Arab Spring of 2011. Several models are specified to study employment decisions based on quarterly administrative firm level data over the period of 2007 to 2012. The data provides information about important firm characteristics such as industry sector, number of hiring and separation, total employment effects and composition of labour force by gender, managerial level and age cohorts. Six models are estimated to investigate hiring, separation, hiring rate, separation rate, mobility, and net-employment. The results indicate presence of continued risk factors in Tunisia's labour market resulting from the global financial crisis in 2008 and the Arab Spring in 2011. Hiring was little changed during this time period, and the results suggest that factors that impact separation decisions remained present in Tunisia's labour market. In addition, the paper looks at various social issues such as youth unemployment and infer on how more efficient policy actions that will further engage the private sector could result in more sustainable positive net-employment and increased labour mobility.
Keywords: E24; J23; J63; 330; hiring; separation; labour mobility; net-employment; informal sector; Tunisia; Arab Spring; global financial crisis